Ecocritics and ecoskeptics : a humanist reading of recent French ecofiction - Krell, Jonathan F., 1952- (Studies in modern and contemporary France., 2020)
Ecocritics and Ecoskeptics examines environmental themes and questions about the evolving relationship between humans and animals in nine modern and contemporary French novels. Considering arguments from both environmentalists and ecoskeptics, it concludes that, far from distancing itself from humanism as it often has, environmentalism must embrace an inclusive and ecological humanism.